A FRAMEWORK FOR SIMULATIONS AND GAMES BASED ON INDIGENOUS KNOWLEDGE AND FOLKLORE TO CREATE DISASTER AWARENESS: COMPARING FROM INDONESIA AND IMPLEMENTING IT IN JAPAN - Mega Mirasaputri Cahyanti; Seno Budhi Ajar (GeoEco, 2025)
Indigenous disaster knowledge and folklore play a crucial role in fostering disaster awareness, yet traditional practices are increasingly being neglected in modern society. Simulation and Gaming (S&G) offers a promising solution to these challenges, particularly in raising unconscious understanding of evacuation procedures during earthquakes and tsunamis, especially for those in vulnerable regions. Despite its potential, no scientific research has yet applied this method in Japan. This study analyses the S&G approach used in Indonesia, inspired by the Smong folklore, which aims to increase awareness of tsunami risks. Building on this, the research proposes a framework for an S&G tailored to Japan, incorporating Namazu folklore and the ancient wisdom of tsunami tendenko. The framework was developed through interviews with key informants, including a game maker from Indonesia, a scholar, and a museum manager in Japan. The initial phase of the framework was created to develop a board game for raising disaster awareness among residence along the Tohoku coastline area. The integration of local folklore which is deeply rooted in local culture and making it more relatable and engaging for community members, offers its effectiveness in enhancing community resilience to tsunamis. The study concludes that this innovative approach will not only work in Japan but could also be adapted by other disaster-prone regions worldwide, offering a versatile tool for improving disaster preparedness and safeguarding vulnerable communities.